HUBUNGAN KOORDINASI MATA DAN KAKI DAN KELENTUKAN OTOT PUNGGUNG TERHADAP KEMAMPUAN SMASH PADA ATLIT SEPAKTAKRAW PPAT CLUB RUMBAI - Suhendar, Agus; Zainur, Zainur; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Based on researchers' observations in the field, it can be obtained from the trainer that the current PPAT Club Rumbai athlete sepaktakraw athletes do not yet show a maximum smash. A smasher often fails to make a hard and sharp smash, besides that the smash is often inaccurate. It is seen that so many balls don't die because they can be dammed by the opponent, the ball hits the net and even the ball comes out of the field. The population is the whole subject of the study.